An Early Discovery Of Fullers' Earth In Arkansas. - J. C. Branner (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1912)
(New York Meeting, February, 1012.) DURING the past two or three years I have seen statements regarding the first discovery of fullers' earth in this country that seem to require correction or modification. One appears again in the Mineral Resources of the United States for 1909, part II., p. 738, where it is said that ? fullers' earth was first discovered in the United States at Quincy, Fla., in 1893." In this connection the following bit of unpublished history concerning fullers' earth in the State of Arkansas is worthy of attention. In April, 1891, when I was State Geologist of Arkansas, a Swede named John Olsen, formerly a copper-miner in Michigan, but then living south of Little Rock, brought me a sample of what he thought was fullers' earth. He reported that it was from near the town of Alexander, the locality being 1 S. 13 W., section 8, SW. quarter of the SE. quarter. My chemist, Dr. R. N. Brackett, analyzed the material, and reported: Per Cent. Silica, . . SiO2., . 63.19 Alumina, . AL2O3, . 18.76 Iron, . Fe203 7.05 Lime, . Ca0 0.78 Magnesia, . . MgO 1.68 Potash, . K2O 0.21 Soda, . . Na2O 1.50 Loss on ignition, . 7.57 100.74 Water at 110° to 115° C. = 7.84. Another sample from about the same locality, also brought by John Olsen, on analysis by Dr. Brackett gave